2023
DOI: 10.3390/biomedicines11092382
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Polymorphism in the Endothelial Homeostasis and Vitamin D Metabolism Genes in the Severity of Coronary Artery Disease

Anastasia Ponasenko,
Anna Sinitskaya,
Maxim Sinitsky
et al.

Abstract: Coronary artery disease (CAD) remains one of the leading causes of cardiovascular morbidity and mortality worldwide. The maintenance of endothelial homeostasis and vitamin D metabolism play an important role in CAD pathogenesis. This study aimed to determine the association of endothelial homeostasis and vitamin D metabolism gene polymorphism with CAD severity. A total of 224 low-risk patients (SYNTAX score ≤ 31) and 36 high-risk patients (SYNTAX score > 31) were recruited for this study. The serum level of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 68 publications
1
0
0
Order By: Relevance
“…The authors found an association with the age of onset of the disease of polymorphism rs243866 of the matrix metalloproteinase 2 gene, and the GG genotype at this locus marked an earlier manifestation of the pathology. This work once again convincingly demonstrates the important medical significance of the genetic variant of matrix metalloproteinases, which has been repeatedly demonstrated in previously performed works [9,10]. Moreover, it indicates the key importance of matrix metalloproteinase genes in the human organism, both in normal and pathological conditions.…”
supporting
confidence: 81%
“…The authors found an association with the age of onset of the disease of polymorphism rs243866 of the matrix metalloproteinase 2 gene, and the GG genotype at this locus marked an earlier manifestation of the pathology. This work once again convincingly demonstrates the important medical significance of the genetic variant of matrix metalloproteinases, which has been repeatedly demonstrated in previously performed works [9,10]. Moreover, it indicates the key importance of matrix metalloproteinase genes in the human organism, both in normal and pathological conditions.…”
supporting
confidence: 81%